Effects of aging, temperature, and time on the ultimate tensile strength of Al 2024 - Benedict Iyida; Azubuike Nwankwo; Thomas Onah (Engineering and Technology Journal, 2025)
This study focuses on the ultimate tensile strength of Al 2024 in that since the past decade, Al 2024 alloy (Al-4.5% Cu-1.5% Mg-0.6% Mn) has been one of the most widely used Al-Cu-Mg-Mn alloys. Therefore, it was subjected to heat treatment, quenching, and artificial aging. The artificial aging temperatures were 1400 °C, 1600 °C, 1800 °C, and 1900 °C, each for the range from 0.5 hr to 9 hr. The ultimate tensile strength of the as-cast after solutionizing and quenching increased from 185 MPa to 199 MPa, representing a 7.6% increase. At 1900 °C aging temperature, the peak value of 348 MPa, representing an 88.1% increase from the as-cast value, was recorded at 6 hr aging time. The drops in ultimate tensile strength values outside the peak aging time of 6 hr were attributed to the precipitation of incoherent and coarse secondary phases in the alloy structure. Ultimate tensile strength values increased at various aging temperatures and aging times, culminating in 482 MPa, which is the semi-maximum overall value at 1800 °C and 6 hr. Aging temperature, representing a 160.5% increase from the as-cast value, while 510 MPa was recorded as the overall maximum ultimate tensile strength at 1400 °C and 8 hr aging time, representing a 175.7% increase from the as-cast value. This was a very considerable enhancement in the mechanical properties of Al 2024 with respect to ultimate tensile strength.